Understanding the Level of Knowledge and Attitudes of Pregnant Women on Use of Complementary and Alternative Medicine (CAM) - Pravati Tripathy; B. Gomathi; Anita Pradhan; Babita Narzary; Jayashree Mahanta; Swarnaprava Samal (International Journal of Midwifery Nursing And Practices, 2023)
Background: The utilization of complementary and alternative medicine (CAM) among pregnant women in India is on the rise. Though the pregnant women are using these therapies, they lack adequate knowledge. It is the responsibility of the health care provider to identify the knowledge to promote healthy practices and to avoid harmful practices. Method: For this investigation, a quantitative method was used. The level of knowledge and attitude of pregnant women regarding the use of complementary and alternative medicines was investigated using a non-experimental, exploratory research methodology. In the antenatal OPD of the IMS & SUM Hospital in Bhubaneswar, Odisha, the study was carried out. The tools used for the study were 1. Demographic questionnaire, 2. Knowledge questionnaire to assess the knowledge on CAM, 3. Attitude scale to assess the attitude of women towards the CAM. Data were gathered through interviews. Each expectant lady gave informed written consent prior to the data collection. SPSS 20 was used to enter and analyse the data. Results: Highest percentage of the women had very good knowledge (64%) and scored between 16-20. More than half of the women (58%) had neutral attitude and scored between 16-30. Significantly favourable link between pregnant women's attitudes and knowledge of complementary and alternative medicine was discovered (r=0.72, p=0.04). Conclusion: Pregnant women are increasingly turning to complementary and alternative treatment. Therefore, it is crucial that healthcare professionals often inquire about CAM use during pregnancy and offer pertinent guidance on CAM use.
Keywords: Complementary and Alternative Medicine; Knowledge; Pregnant women; attitude